Թորոս Ռոսլին. կյանքն ու արվեստը - Իրինա Դրամբյան (ՀՀ ԳԱԱ հրատ.)
Комплексное исследование колофонов рукописей Тороса Рослина и самого художественного наследия мастера выявило ряд важных биографических данных, прежде всего, приблизительную дату его рождения (около 1230 г.) и факт несомненного посещения им соседней Антиохии, одного из крупнейших эллинистических центров, еще сохранявших в эпоху Рослина множество памятников античного зодчества и монументальной живописи. Comprehensive investigation of colophons of Toros Roslin’s manuscripts and the very artistic heritage of the master reveals a number of important data of his biography. First and foremost it is an approximate date of his birth (about 1230) and the undoubted fact that he visited the neighbouring Antioch, one of the most important Hellenistic centers, where a lot of monuments of ancient architecture and monumental painting still persisted in the era of Roslin.
Keywords: Biography; Auxiliary Sciences of History; N Fine Arts; ND Painting